1997
DOI: 10.1523/jneurosci.17-04-01350.1997
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Gated Ion Channel Subunit Partnerships: GABAAReceptor α6Subunit Gene Inactivation Inhibits δ Subunit Expression

Abstract: Cerebellar granule cells express six GABAA receptor subunits abundantly (alpha1, alpha6, beta2, beta3, gamma2, and delta) and assemble various pentameric receptor subtypes with unknown subunit compositions; however, the rules guiding receptor subunit assembly are unclear. Here, removal of intact alpha6 protein from cerebellar granule cells allowed perturbations in other subunit levels to be studied. Exon 8 of the mouse alpha6 subunit gene was disrupted by homologous recombination. In alpha6 -/- granule cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
288
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(311 citation statements)
references
References 60 publications
23
288
0
Order By: Relevance
“…The results reported here were obtained from cerebellar granule cells, a cell type for which there is strong evidence that receptors containing α6 and δ subunits are extrasynaptic 16,19,36 and are required for tonic GABA current 20,21 . We demonstrate that tonic current is facilitated by low ethanol concentrations and, in addition, identify a variant of α6 (α6-100Q) that renders tonic current carried by α6β3δ GABARs much more sensitive to ethanol.…”
Section: Link Between Tonic Inhibition and Behaviormentioning
confidence: 80%
See 1 more Smart Citation
“…The results reported here were obtained from cerebellar granule cells, a cell type for which there is strong evidence that receptors containing α6 and δ subunits are extrasynaptic 16,19,36 and are required for tonic GABA current 20,21 . We demonstrate that tonic current is facilitated by low ethanol concentrations and, in addition, identify a variant of α6 (α6-100Q) that renders tonic current carried by α6β3δ GABARs much more sensitive to ethanol.…”
Section: Link Between Tonic Inhibition and Behaviormentioning
confidence: 80%
“…It is possible that Gabra6 −/− mice will show less impairment on the rotarod in a lower range of ethanol doses, but there are reasons to believe that ethanol sensitivity of knockout mice may be complicated. First, the expression of GABAR subunits α1, β2, γ2 and δ is changed markedly in Gabra6 −/− mice 19,36,43 , and other potential ethanol targets such as two-pore domain K + channels 20 show increased function in granule cells, making it difficult to rule out compensatory changes in Gabra6 −/− mice. Second, differences in cerebellum-dependent behavior at moderate ethanol doses may be obscured in the Gabra6 −/− mouse by other more abundant and widely expressed ethanol targets.…”
Section: Gabra6 100q Allele and Behavioral Sensitivity To Ethanolmentioning
confidence: 99%
“…Unexpectedly, this mutation caused the disappearance of the d subunit protein (74). However, since mRNA levels for the d subunit were not affected, this finding suggested that the d subunit protein requires the a6 subunit for assembly in a receptor complex and is degraded rapidly in the absence of this mandatory partner.…”
Section: Effects Of Targeted Subunit Gene Deletion On Cerebellar Gabamentioning
confidence: 90%
“…The antibody against α4 subunit (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) has been characterized previously [1,12,32]. The antibodies against the γ2 (1-33) and δ (1-44) subunit of the GABA A receptor have been characterized extensively in the past by immunoprecipitation, Western blot, and immunohistochemistry [11,[19][20][21][22]32]. The antibodies against α1, α4, γ2 and δ were characterized by Western blot.…”
Section: Antibodiesmentioning
confidence: 99%
“…For example, electron microscopic examination of GABAergic synapses in cerebellum and hippocampus reveals aggregates of α1, β2/3, and γ2 subunits at GABAergic synapses [16,19]. Conversely, post-embedding immunogold electron microscopic studies of cerebellar granule cells have demonstrated that α6 and δ subunits are expressed in the extrasynaptic membrane [11,19].…”
Section: Introductionmentioning
confidence: 99%